“Eu sou uma conversa”: tessituras entre o queer e o plasmático nos corpos animados de Steven Universe - Lage, Mariana Pitombeira (2022)
The present dissertation proposed to analyze the queer theme in the plasmatic animation of the Steven Universe series. Bodies drawn in animation works are malleable, being able to stretch, shrink, melt, twist and bend, a property that Eisenstein (2017) names plasmaticity. This work investigated ways in which the Steven Universe series appropriates this corporal malleability for the construction of queer characters and relationships, going beyond the heteronormativity commonly present in media products aimed at children. To analyze the images, we took as inspiration the Atlas Mnemosyne, by the German historian Aby Warburg, as well as the comprehensive filmic analysis of the serial narrative proposed by Larissa Azubel (2018). The queer theory and the plasmatic characteristics of cartoons were approached from references such as Guacira Lopes Louro (2020), Richard Miskolci (2012), Judith Butler (2019), Paul Preciado (2019), as well as Sergei Eisenstein (2017) and Thomas Lamarre (2013). The notion of masculinity in the protagonist Steven was based on the studies of Connell (2005) and Kimmel (2006), stressing the hegemonic heteronormative perspective. In addition, the kinship ties (HESTON, 2013; WESTON, 1991) of Steven's family were analyzed, from the perspective of queer utopia (MUÑOZ, 2009) and failure (HALBERSTAM, 2020). In the magical universe of Steven Universe, the concept of fusion stands out, as in which the characters are characterized by physically modifying their bodies, in other beings and objects, through the discussion made by Haraway (2009), Cooley (2020) and Ristola (2020). As a result, we saw that in Steven Universe the plasmaticity of the animation is explored in a queer potential for the making of a narrative that performs nowadays a queer utopia, promoting the possibilities of experiences outside the heteronormativity. KEYWORDS: Steven Universe; queer; plasmacticity; fusion; masculinity